Influence of Produck Quality, Religuisity an Promotion on Decition to Save in Islamic Bank - Rustina Dewi Werdiasih; Esih Jayanti (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Intense competition in the banking sector requires banks to always innovate in running their business. Currently, Islamic banks have to compete with conventional banks that have experience and are more stable in terms of resource capabilities, but Islamic banks have the opportunity to develop more widely because of public awareness of a sharia-compliant lifestyle. This study aims to analyze the effect of product quality, level of religiosity and promotion on customer decisions to save money in Islamic banks. This research was conducted using a survey method, collecting data with Islamic bank customers as respondents. The sampling technique is purposive sampling method. The number of samples is 100 Islamic Bank customersData analysis using t test and F test to prove the hypothesis. Based on the results of data analysis, it is found that there is no influence of product quality on the decision to deviate money in Islamic banks. The results of the study indicate that there is an influence of religiosity on the decision to save money in Islamic banks. There is a promotion effect on the decision to save money in Islamic banks. Based on these findings, Islamic banks need to improve the quality of their products to attract customers to save money in Islamic banks.